An improved dynamic quantization scheme for uncertain linear networked control systems. (June 2018) - Wang, Yilin; Yu, Shuanghe
Abstract: A Lyapunov–Krasovskii Functional (LKF)-based dynamic quantization strategy was innovated in the paper 'Dynamic quantization of uncertain linear networked control systems'. Though effective and comprehensive, it is conservative in terms of converging speed and the upper bound of the system states. This paper aims at improving the zooming-in algorithm to bring faster convergence of the closed-loop system. A more accurate upper bound for the system states is also obtained with smaller initial value and faster decay rate. The effectiveness of the improvements is illustrated by simulation.